Physiological and pharmacological actions of glucagon like peptide-1 (GLP-1) in domestic animals - Model, Jorge Felipe Argenta (2022)
Analogues of glucagon like peptide-1 (GLP-1) and other drugs that increase this peptide half-life are used worldwide in human medicine to treat type 2 diabetes mellitus (DM) and obesity. These molecules can increase insulin release and satiety, interesting effects that could also be useful in the treatment of domestic animals pathologies, however their use in veterinary medicine are still limited. Considering the increasing incidence of DM and obesity in cats and dogs, the aim of this review is to summarize the available information about the physiological and pharmacological actions of GLP-1 in domestic animals and discuss about its potential applications in veterinary medicine. In diabetic dogs, the use of drugs based on GLP-1 actions reduced blood glucose and increased glucose uptake, while in diabetic cats they reduced glycemic variability and exogenous insulin administration. Thus, available evidence indicates that GLP-1 based drugs could become alternatives to DM treatment in domestic animals. Nevertheless, current data do not provide enough elements to recommend these drugs widespread clinical use.